Development and Validation of a Delay Assessment Matrix for Road and Highway Projects - Reddy, Harish; M S, Nagakumar (PREPARE@u® | IEI Conferences, 2021)
The study aims to gather information and assess the extent of delays and their impact on road and highway projects in India. The objective is to develop a delay assessment matrix for easy quantification of delay causing factors on project duration. A mixed method approach was used for data collection wherein information was gathered through literature review, questionnaire survey, interviews and responses under RTI act. The collected information was screened, verified and analyzed using statistical tools. Factor analysis was employed to arrive at a final list of 22 factors grouped in a 3x3 matrix having probability of occurrence vs. impact on project duration as the axes. The model was tested on a recently completed highway project using Monte Carlo simulation technique. The result of simulation was the increase in project schedule due to the occurrence of delays in the project in accordance with the specified probability and impact. The simulated duration of the project was in the range of 1095 days, 1229 days, and 1375 days for low, moderate and severe conditions respectively. The actual project duration was reported at 1116 days against contracted duration of 910 days. The simulated duration is found to be in close agreement with the actual duration of the project.